El papel del petróleo en el crecimiento económico de colombia: un análisis de las tendencias y relaciones durante el periodo 2000-2021 (2023)
The thesis entitled "The role of oil in Colombia's economic growth: an analysis of trends and relationships during the period 2000-2021" aims to analyze the importance of oil and its derivatives in Colombian economic growth during the aforementioned period. For this purpose, two specific objectives were established: to contrast data on total exports and exports of oil and its derivatives in the period 2000-2021, and to show the relationship of international oil prices with Colombian economic growth during the years 2000-2020.